Galvanic Replacement: Galvanically Replaced, Single‐Bodied Lithium‐Ion Battery Fabric Electrodes (Adv. Funct. Mater. 16/2020). (20th April 2020) - Woo, Sang‐Gil; Yoo, Sijae; Lim, Si‐Hyoun; Yu, Ji‐Sang; Kim, Kyungbae; Lee, Jaegab; Lee, Donggue; Kim, Jae‐Hun; Lee, Sang‐Young
Abstract : In article number 1908633, Jae‐Hun Kim, Sang‐Young Lee, and co‐workers present a galvanically replaced single‐bodied Sn@Ni fabric electrode as a new approach for developing high‐performance lithium‐ion battery (LIB) electrodes with exceptional redox reaction kinetics and omnidirectional deformability. Benefiting from the chemical/structural uniqueness, the single‐bodied Sn@Ni fabric electrode provides significant improvements in electrochemical performance and mechanical flexibility, which lie far beyond those attainable with conventional LIB electrode technologies.